Sistem Pendukung Keputusan Pemilihan Tipe Rumah PT. Niaga Guna Kencana Jambi - Februssi, Aditya; Fachruddin, Fachruddin (Jurnal Manajemen Sistem Informasi, 2023)
The development of information technology has influenced the property industry, and its usage is increasingly being enhanced by companies to survive and capitalize on business opportunities. Basic human needs such as housing have become a growing business with the presence of housing developers. PT Niaga Guna Kencana is one of the housing developers offering a unique and modern concept with a harmonious balance between buildings and the environment. However, potential buyers face difficulties in choosing the right type of house due to a lack of information and specific criteria. Therefore, this research will analyze and design a prototype of a decision support system for house type selection using the Analytical Hierarchy Process (AHP) method at PT Niaga Guna Kencana Jambi, with a focus on criteria such as price, location, facilities, and house type. The aim of this research is to develop a decision support system that helps potential buyers determine the most suitable place to live based on specific criteria and their levels of importance. This research is limited to the use of the AHP method, potential buyers of residential houses, criteria such as price, location, facilities, and house type, HTML prototype, and the research object located at Citraland NGK Cluster Grand Mansion housing complex in Mayang Mangurai.